Neurocognitive functioning in MDR-TB patients with and without HIV in KwaZulu-Natal, South Africa - Ramlall, Suvira (Trop Med Int Health, 2020)
OBJECTIVES: Optimising medication adherence is one of the essential factors in reversing the tide of a TB-HIV syndemic in sub-Saharan Africa, especially South Africa. Impairment in key neurocognitive domains may impair patients’ ability to maintain adherence to treatment, but the level of cognition and its relationship to HIV status has not been examined in individuals with drug-resistant TB. We therefore investigated performance on several key neurocognitive domains in relationship to HIV status in a multidrug-resistant tuberculosis patients (MDR-TB) sample. METHODS: We enrolled microbiologically confirmed MDR-TB inpatients at a TB-specialist referral hospital in KwaZulu-Natal province, South Africa. We collected cross-sectional data on sociodemographic, clinical and neurocognitive function (e.g. attention, memory, executive functioning, language fluency, visual-spatial, eye–hand coordination). For the primary analysis, we excluded participants with major depressive episode/substance use disorder (MDE/SUD). We fitted adjusted Poisson regression models to explore the association between HIV and neurocognitive function. RESULTS: We enrolled 200 people with MDR-TB; 33 had MDE/SUD, and data of 167 were analysed (151 HIV+, 16 HIV−). The mean age of participants was 34.2 years; the majority were female (83%), and 53% had not completed secondary school. There was evidence of impaired neurocognitive functioning across all domains in both HIV+/− study participants. Based on the regression analyses, individuals with co-infection (MDR-TB/HIV+), as well as those who had longer duration of hospital stays experienced significantly lower cognitive performance in several domains. Poor cognitive performance was significantly related to older age and lower educational attainment. The presence of major depression or substance use disorders did not influence the significance of the findings. CONCLUSIONS: Adults with MDR-TB have significant neurocognitive impairment, especially if HIV positive. An integrated approach is necessary in the management of MDR-TB as cognitive health influences the ability to adhere to chronic treatment, clinical outcomes and functionality.